Political economy and media production: a reply to Dwyer. (July 2016) - Murdock, Graham; Golding, Peter
This is a response to an article by Paul Dwyer in this Journal which makes several claims about the nature and impact of the political economy approach to the analysis of media and communications. We argue that Dwyer's article misunderstands or is unaware of the history of this approach, and quite fundamentally misconstrues its central tenets. Our response explains how, in capitalist societies, media organisations are integrated into general processes of accumulation, how they exercise power, and how their strategies shape the communications landscape. We explain how the critical political economy approach actually works and illustrate how it has been deployed for concrete analysis in ways that Dwyer seems unaware of. Analysis of shifts in the organisation of capitalism and of their consequences for the structure of cultural production is essential alongside detailed research into how shifting webs of pressure and opportunity impinge on the everyday business of crafting cultural goods in specific cultural industries. We argue that, contra Dwyer, contemporary analysis has a rich legacy of work in both areas on which to build.